Electrolyte and lithium battery containing same

The lithium-ion battery is solved at high voltage and high temperature by using electrolytes of fluorovinyl carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentan and acid anhydride compounds in lithium-ion batteries. The problems of gas bloating, circulating attenuation and thickness increase under conditions have achieved improvements in the high temperature stability and circulation performance of the battery.

CN119495817AActive Publication Date: 2025-02-21ZHANGJIAGANG GUOTAI HUARONG NEW CHEM MATERIALS CO LTD
View PDF 14 Cites 0 Cited by

Patent Information

Application Number
CN202311050232.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-21
Estimated Expiration
2043-08-21

AI Technical Summary

Technical Problem

Existing lithium-ion batteries have problems such as gas inflation, circulation attenuation and thickness increase under high voltage and high temperature conditions, resulting in a sharp "dive" battery capacity and an increase in battery internal resistance.

Method used

Using an electrolyte containing fluorovinyl carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentan and acid anhydride compounds, the coordinated combination of these additives can inhibit the lithium battery from being at high voltage. The side reactions at high temperatures improve the battery's high temperature stability and circulation performance.

Benefits of technology

It effectively suppresses the gas inflation, circulation attenuation and thickness increase of lithium batteries under high voltage and high temperature conditions, improves the rate performance of the battery, and improves the high-temperature shelving capacity retention rate and circulation retention rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004404100080000041
    Figure BDA0004404100080000041
  • Figure BDA0004404100080000091
    Figure BDA0004404100080000091
  • Figure BDA0004404100080000101
    Figure BDA0004404100080000101
Patent Text Reader

Abstract

The invention relates to an electrolyte and a lithium battery containing the electrolyte. In order to solve the problem of poor electrochemical performance of a lithium battery under high voltage, the invention provides an electrolyte which comprises an organic solvent, a lithium salt and an additive, and the additive comprises fluoroethylene carbonate, 1, 2, 3, 4, 5-penta (cyanoethoxy) pentane and an anhydride compound. The electrolyte provided by the invention is simple in component, and through the synergistic cooperation of fluoroethylene carbonate, 1, 2, 3, 4, 5-penta (cyanoethoxy) pentane and anhydride compounds, the inflation, cycle attenuation and thickness increase of the lithium battery under high voltage (4.5 V and above) and high temperature conditions can be effectively inhibited, and the rate capability of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrolyte and a lithium battery containing the electrolyte. Background Art

[0002] With the emergence of emerging consumer areas such as mobile phones, tablets, smart wearables, and ETC, lithium-ion batteries have shown great advantages with their high energy density and long cycle life. However, with the continuous diversification of the functions of corresponding equipment and the continuous increase in the power consumption of power modules, conventional lithium-ion batteries have been difficult to meet the needs of users. In order to improve the user experience, the development direction of lithium-ion batteries has become increasingly clear, that is, to increase the energy density as much as possible or achieve fast charging under safe conditions.

[0003] In order to improve energy density, the industry is currently developing from three main aspects. First, seek new material systems, such as lithium cobalt oxide, lithium-rich manganese-based, ternary high nickel and other positive electrode materials, silicon carbon and other negative electrode materials; second, increase the cut-off charging voltage of existing materials, such as lithium cobalt oxide batteries above 4.5V, ternary batteries above 4.4V, etc.; third, by changing the battery process, increasing the surface density and compaction density or using thinner current collectors, tapes and aluminum plastic shells. In order to achieve fast charging, fast-charging lithium-ion batteries came into being, from the initial 0.2C charging, to the later 2C charging, and even 5C charging.

[0004] In the digital field that requires high volume energy density, the design concept of lithium batteries is high-voltage lithium cobalt oxide & silicon-carbon negative electrode. The voltage of commercial lithium cobalt oxide batteries has gradually increased from the initial 4.2V to 4.5V and above, but with the increase in voltage, existing lithium cobalt oxide batteries have shown certain negative effects. For example, the presence of dangling bonds and unsaturated coordination relationships on the surface of the material will make its reaction activity significantly higher than that of the bulk phase. When charging a lithium cobalt oxide battery, the following reaction process will occur:

[0005] (1) The positive electrode material begins to remove lithium from the surface;

[0006] (2) After delithiation occurs, the oxygen atoms in the Li layer lose their barrier and repel each other, resulting in unstable surface structure;

[0007] (3) Continuous lithium removal promotes gas overflow from surface lattice activity;

[0008] (4) The outflow of gas causes the surface Co atoms to become less stable and dissolve;

[0009] (5) The dissolved high-valent Co element will also oxidize the electrolyte and participate in the electrolyte chemical reaction.

[0010] Solid-liquid interface side reactions are an inevitable problem in the development of lithium batteries. The chemical window of the electrolyte currently used is usually lower than 4.5V. When the charge cut-off voltage is higher than 4.5V, the electrolyte will undergo oxidation and decomposition on the battery surface. This process causes the battery capacity to "dive" sharply. At the same time, the products of oxidation and decomposition also cover the surface of the electrode material, increasing the internal resistance of the battery. The boundary of the products of the surface side reactions catalyzed by free transition metal elements causes the electrode material to maintain a high-activity state, which poses a hidden danger.

[0011] Therefore, it is necessary to develop an electrolyte with good electrochemical performance at high voltage. Summary of the invention

[0012] The object of the present invention is to provide an electrolyte having good high temperature stability and cycle performance under high voltage.

[0013] The second object of the present invention is to provide a lithium battery comprising the electrolyte.

[0014] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0015] An electrolyte comprises an organic solvent, a lithium salt and an additive, wherein the additive comprises fluoroethylene carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentane and an acid anhydride compound.

[0016] Preferably, the 1,2,3,4,5-penta(cyanoethoxy)pentane accounts for 0.1-7% of the total mass of the electrolyte, more preferably 0.5-5%, and even more preferably 3-5%, such as 3%, 3.5%, 4%, 4.5% or 5%. In the present invention, the 1,2,3,4,5-penta(cyanoethoxy)pentane can be prepared by mixing xylitol and sodium ethoxide, and then adding acrylonitrile to react; wherein the reaction temperature is preferably 80-100°C.

[0017] Preferably, the acid anhydride compound is a cyclic carboxylic acid anhydride.

[0018] Further preferably, the acid anhydride compound is selected from the compound represented by structural formula A and / or the compound represented by structural formula B, wherein structural formula A is Structural formula B is R 1 , R 2 , R 3 and R 4 Each of them is independently selected from H, an alkyl group having 1 to 3 carbon atoms, or a phenyl group. The alkyl group having 1 to 3 carbon atoms may be, for example, a methyl group, an ethyl group, or a propyl group.

[0019] In some specific embodiments, the acid anhydride compound is selected from one or more of 2-methylmaleic anhydride, 2,3-dimethylmaleic anhydride, phenyl maleic anhydride, and succinic anhydride.

[0020] Preferably, the acid anhydride compound accounts for 0.1-1% of the total mass of the electrolyte, more preferably 0.3-0.5%, for example 0.3%, 0.35%, 0.4%, 0.45% or 0.5%.

[0021] Preferably, the fluoroethylene carbonate accounts for 0.1-10% of the total mass of the electrolyte, more preferably 2-8%, for example 2%, 3%, 4%, 5%, 6%, 7%, 8%, etc.

[0022] Preferably, the additives also include other additives, which include one or more of vinyl ethylene carbonate, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, adiponitrile, succinonitrile, 1,2-bis(2-cyanoethoxy)ethane, 1,4-dicyano-2-butene, 1,2,3-tris(2-cyanoethoxy)propane, sebaconitrile, and 2-methylglutaronitrile.

[0023] Preferably, each of the other additives accounts for 0.1 to 8% of the total mass of the electrolyte.

[0024] Preferably, the organic solvent is a mixture of cyclic esters and chain esters, the cyclic ester is one or more of γ-butyrolactone, ethylene carbonate, propylene carbonate, and fluoroethylene carbonate; the chain ester is one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methylpropyl carbonate, methyl propionate, ethyl propionate, propyl propionate, methyl acetate, ethyl acetate, propyl acetate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl fluoropropionate, ethyl fluoropropionate, and ethyl fluoroacetate.

[0025] In some embodiments, the organic solvent is ethylene carbonate, propylene carbonate, diethyl carbonate, ethyl propionate and propyl propionate. Conventional carbonate solvents are easily catalytically decomposed under high voltage conditions. The present invention effectively inhibits the catalytic decomposition of carbonate solvents through the synergistic combination of the above additives, thereby reducing the gas production of the battery and the dissolution of metal ions.

[0026] Further preferably, the organic solvent further comprises ethyl fluoroacetate, and the ethyl fluoroacetate may be, for example, 2,2-difluoroethyl acetate.

[0027] Preferably, the lithium salt is lithium hexafluorophosphate.

[0028] Preferably, the concentration of the lithium salt is 0.8-3 mol / L.

[0029] Preferably, the additive further includes a lithium salt additive, and the lithium salt additive is one or more of lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorophosphate, lithium difluorooxalatoborate, lithium trifluoromethylsulfonate, and lithium bis(trifluorosulfonyl)imide.

[0030] Further preferably, the lithium salt additive accounts for 0.1-5% of the total mass of the electrolyte.

[0031] The second object of the present invention is to provide a lithium battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and the electrolyte as described above.

[0032] Preferably, the active material of the positive electrode sheet is lithium cobalt oxide, and the charging cut-off voltage of the lithium battery can reach 4.5V and above.

[0033] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:

[0034] The electrolyte components of the present invention are simple. Through the coordinated combination of fluoroethylene carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentane and anhydride compounds, the electrolyte can effectively inhibit the gas expansion, cycle attenuation and thickness increase of the lithium battery under high voltage (4.5V and above) and high temperature conditions, and improve the rate performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 is the C NMR spectrum of 1,2,3,4,5-penta(cyanoethoxy)pentane;

[0036] Figure 2 This is the H NMR spectrum of 1,2,3,4,5-penta(cyanoethoxy)pentane. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with the examples. However, the present invention is not limited to the following examples. The implementation conditions used in the examples can be further adjusted according to the different requirements of specific use, and the implementation conditions not specified are conventional conditions in the industry. The technical features involved in each embodiment of the present invention can be combined with each other as long as they do not conflict with each other.

[0038] In the present invention, the structural formula of 1,2,3,4,5-penta(cyanoethoxy)pentane is shown below.

[0039]

[0040] 1,2,3,4,5-penta(cyanoethoxy)pentane can be prepared by mixing xylitol and sodium ethoxide and then adding acrylonitrile to react.

[0041] As a preferred example, the preparation method of 1,2,3,4,5-penta(cyanoethoxy)pentane is as follows:

[0042] 152g xylitol and 6.8g sodium ethoxide were mixed and heated to 90°C and stirred for 2 hours. Then 477g acrylonitrile was slowly added dropwise and stirred. The mixture was reacted for 12 hours. After cooling to room temperature, 6000g ethanol was added and stirred evenly. The mixture was filtered to obtain a residue. The residue was recrystallized and purified with ethyl acetate and n-hexane to obtain a finished product with a purity of >99%. For the NMR spectrum, see Figure 1 and Figure 2 .

[0043] Unless otherwise specified, the reagents used in the examples and comparative examples of the present invention are all commercially available products. In the examples and comparative examples of the present invention, diethyl carbonate is referred to as DEC, ethylene carbonate is referred to as EC, propylene carbonate is referred to as PC, ethyl propionate is referred to as EP, propyl propionate is referred to as PP, and 2,2-difluoroethyl acetate is referred to as DFEA.

[0044] Example 1

[0045] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.1 wt % of succinic anhydride were added to the electrolyte to prepare an electrolyte.

[0046] Example 2

[0047] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of succinic anhydride were added to the electrolyte to prepare an electrolyte.

[0048] Example 3

[0049] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6Then, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.5 wt % of succinic anhydride were added to the electrolyte to prepare an electrolyte.

[0050] Example 4

[0051] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 1 wt % of succinic anhydride were added to the electrolyte to prepare an electrolyte.

[0052] Example 5

[0053] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.5 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0054] Example 6

[0055] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.5 wt % of 2,3-dimethylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0056] Example 7

[0057] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.5 wt % of phenyl maleic anhydride were added to the electrolyte to prepare an electrolyte.

[0058] Example 8

[0059] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 1 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0060] Example 9

[0061] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0062] Example 10

[0063] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 5 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0064] Embodiment 11

[0065] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 7 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0066] Example 12

[0067] In an argon-filled glove box (H2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 1 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0068] Example 13

[0069] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 2 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0070] Embodiment 14

[0071] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 8 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0072] Embodiment 15

[0073] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 10 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0074] Example 16

[0075] In an argon-filled glove box (H 2O content <10ppm), DFEA, DEC, EC, PC, EP and PP were mixed in a volume ratio of 1:1:2:1:2:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0076] Embodiment 17

[0077] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 0.5 wt % of lithium difluorooxalatoborate, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0078] Comparative Example 1

[0079] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 , to obtain an electrolyte.

[0080] Comparative Example 2

[0081] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate and 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane were added to the electrolyte to prepare an electrolyte.

[0082] Comparative Example 3

[0083] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6Then, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane) and 0.3 wt % of succinic anhydride were added to the electrolyte to prepare an electrolyte.

[0084] Comparative Example 4

[0085] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate and 0.3 wt % of succinic anhydride were added to the electrolyte to prepare an electrolyte.

[0086] Comparative Example 5

[0087] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0088] Comparative Example 6

[0089] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 4 wt % of fluoroethylene carbonate, 1 wt % of 1,2,3,4-tetra(cyanoethoxy)butane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0090] Comparative Example 7

[0091] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0092] Application Example Group A

[0093] Preparation of lithium cobalt oxide graphite battery:

[0094] (1) Positive electrode active material 4.5V lithium cobalt oxide

[0095] (2) Negative electrode active material artificial graphite

[0096] (3) Diaphragm PP / PE / PP (polypropylene / polyethylene / polypropylene) composite film

[0097] The electrolytes prepared in the above-mentioned Examples 1 to 17 and Comparative Examples 1 to 7 are respectively assembled with the positive electrode sheet, the negative electrode sheet and the separator into a lithium cobalt oxide graphite battery. The assembly method refers to the prior art and is not specifically limited in the present invention.

[0098] Performance Test:

[0099] (1) Capacity retention and battery swelling rate after 4 hours at 85°C

[0100] The above-mentioned lithium cobalt oxide graphite battery was charged to 4.5V at 1C under constant current / constant voltage (CC / CV) conditions at 25°C, then placed in an oven at 85°C for 4 hours, and then discharged to 3.0V at 1C, and the capacity and battery thickness after being placed at 85°C for 4 hours were tested; the capacity and battery thickness of the above-mentioned battery after being charged under the same conditions, not placed at high temperature, and discharged under the same conditions were tested. Among them, the capacity retention rate of the above-mentioned battery after being placed at 85°C for 4 hours is equal to the capacity after being placed at high temperature for 4 hours divided by the capacity without being placed at high temperature; the battery swelling rate after being placed at 85°C for 4 hours is equal to the difference between the battery thickness after placing and the battery thickness before placing divided by the battery thickness before placing.

[0101] (2) 45℃ 200-cycle capacity retention

[0102] At 45°C, constant current / constant voltage (CC / CV) conditions, the battery was charged to 4.5V at 1C, and then discharged to 3.0V at 1C. The battery capacity after the first charge and discharge and after 200 cycles of charge and discharge were tested respectively. The 200-cycle capacity retention rate at 45°C is equal to the battery capacity after 200 cycles of charge and discharge divided by the battery capacity after the first charge and discharge.

[0103] (3) 50% SCO, 2C10s DCR

[0104] The DCR test method of 50% SCO, 2C10s is: the ratio of the voltage difference to the current when the battery is discharged at 2C constant current for 10S at 50% SCO state of charge.

[0105] The relevant performance test data of the above-mentioned lithium cobalt oxide graphite battery are shown in Table 1 below.

[0106] Table 1

[0107]

[0108]

[0109] Embodiment 18

[0110] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 0.5 wt % of lithium difluorooxalatoborate, 2 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0111] Embodiment 19

[0112] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 0.5 wt % of lithium difluorooxalatoborate, 4 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0113] Embodiment 20

[0114] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 0.5 wt % of lithium difluorooxalatoborate, 6 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0115] Embodiment 21

[0116] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6Then, 0.5 wt % of lithium difluorooxalatoborate, 8 wt % of fluoroethylene carbonate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0117] Comparative Example 8

[0118] In an argon-filled glove box (H 2 O content <10ppm), DEC, EC, PC, EP and PP were mixed evenly in a volume ratio of 1:2:1:3:3, and 1.2 mol / L LiPF 6 Then, 0.5 wt % of lithium difluorooxalatoborate, 3 wt % of 1,2,3,4,5-penta(cyanoethoxy)pentane and 0.3 wt % of 2-methylmaleic anhydride were added to the electrolyte to prepare an electrolyte.

[0119] Application Example Group B

[0120] Preparation of lithium cobalt oxide silicon oxygen carbon battery:

[0121] (1) Positive electrode active material 4.5V lithium cobalt oxide

[0122] (2) The active material of the negative electrode is silicon-oxygen-carbon, with a capacity of 450 mAh / g

[0123] (3) Diaphragm PP / PE / PP composite film

[0124] The electrolytes prepared in the above-mentioned Examples 18 to 21 and Comparative Example 8 are respectively assembled with the positive electrode sheet, the negative electrode sheet and the separator into a lithium cobalt oxide silicon oxygen carbon battery. The assembly method refers to the prior art and is not specifically limited in the present invention.

[0125] The performance test data of the above-mentioned lithium cobalt oxide silicon oxygen carbon battery is shown in Table 2. The performance test method is as described above and will not be repeated here.

[0126] Table 2

[0127]

[0128] By comparing Examples 1 to 17 and Comparative Examples 1 to 5, it is found that the combined use of three additives with different functions, namely, fluoroethylene carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentane and acid anhydride, enables the high-voltage LCO system lithium-ion battery to have better high-temperature stability and cycle performance at high temperatures.

[0129] By comparing Examples 1 to 4, it is found that when fluoroethylene carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentane and succinic anhydride are added at the same time, as the amount of succinic anhydride increases, the high temperature shelf capacity retention rate and cycle retention of the battery first increase and then decrease, and the high temperature shelf swelling rate and battery internal resistance (DCR) first decrease and then increase. In general, when the amount of succinic anhydride is 0.1-1wt%, the battery performance is better, and when the amount of succinic anhydride is 0.3-0.5wt%, the battery performance is better.

[0130] By comparing Example 3 with Examples 5 to 7, it was found that when fluoroethylene carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentane and acid anhydride were added simultaneously and the contents of each component were the same, the battery with 2-methylmaleic anhydride, 2,3-dimethylmaleic anhydride or phenylmaleic anhydride had better high-temperature shelf capacity retention rate and cycle retention rate than the battery with succinic anhydride, but the battery swelling rate and battery internal resistance with 2,3-dimethylmaleic anhydride or phenylmaleic anhydride were higher than those with succinic anhydride.

[0131] By comparing Examples 8 to 11, it is found that when fluoroethylene carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentane and 2-methylmaleic anhydride are added at the same time, as the amount of 1,2,3,4,5-penta(cyanoethoxy)pentane increases, the high temperature storage capacity retention rate and cycle retention of the battery first increase and then decrease, the battery swelling rate shows a downward trend, but the battery internal resistance shows an upward trend. In general, when the amount of 1,2,3,4,5-penta(cyanoethoxy)pentane is 1-7wt%, the battery performance is better, and when the amount of 1,2,3,4,5-penta(cyanoethoxy)pentane is 3-5wt%, the battery performance is better.

[0132] By comparing Example 9 with Examples 12 to 15, it is found that when fluoroethylene carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentane and 2-methylmaleic anhydride are added simultaneously, as the amount of fluoroethylene carbonate increases, the high temperature storage capacity retention rate and cycle retention of the battery first increase and then decrease, the swelling of the battery first decreases and then increases, and the internal resistance of the battery first decreases and then increases. In general, when the amount of fluoroethylene carbonate is 1 to 10wt%, the performance of the battery is better, and when the amount of fluoroethylene carbonate is 2 to 8wt%, the performance of the battery is better.

[0133] By comparing Example 9 and Example 16, it is found that the addition of DFEA can improve the electrochemical performance of the battery.

[0134] By comparing Example 9 and Example 17, it is found that the addition of lithium difluorooxalatoborate can improve the swelling rate of the battery, but will slightly increase the internal resistance, and has little effect on the high-temperature storage capacity retention rate and cycle retention rate of the battery.

[0135] By comparing Examples 18 to 21 and Comparative Example 8, it was found that when three additives with different functions, namely, fluoroethylene carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentane and acid anhydride, were present at the same time, adding lithium difluorooxalatoborate had a better effect, and with the increase in the amount of lithium difluorooxalatoborate added, the high-temperature shelf capacity retention rate and cycle retention rate of the battery were improved, and the swelling rate and battery internal resistance decreased.

[0136] The above detailed description of the present invention is intended to enable persons familiar with the art to understand the contents of the present invention and implement them. It does not limit the protection scope of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the protection scope of the present invention.

Claims

1. An electrolyte comprising an organic solvent, a lithium salt and an additive, characterized in that: The additives include fluoroethylene carbonate, 1,2,3,4,5-penta(cyanoethoxy)pentane and anhydride compounds.

2. The electrolyte according to claim 1, characterized in that: The 1,2,3,4,5-penta(cyanoethoxy)pentane accounts for 0.1-7% of the total mass of the electrolyte.

3. The electrolyte according to claim 2, characterized in that: The 1,2,3,4,5-penta(cyanoethoxy)pentane accounts for 1-5% of the total mass of the electrolyte.

4. The electrolyte according to claim 1, characterized in that: The acid anhydride compound is a cyclic carboxylic acid anhydride.

5. The electrolyte according to claim 4, characterized in that: The acid anhydride compound is selected from one or more of 2-methylmaleic anhydride, 2,3-dimethylmaleic anhydride, phenyl maleic anhydride, and succinic anhydride; and / or, The acid anhydride compound accounts for 0.1-1% of the total mass of the electrolyte.

6. The electrolyte according to claim 5, characterized in that: The acid anhydride compound accounts for 0.3-0.5% of the total mass of the electrolyte.

7. The electrolyte according to claim 1, characterized in that: The fluoroethylene carbonate accounts for 0.1-10% of the total mass of the electrolyte.

8. The electrolyte according to claim 1, characterized in that: The organic solvent is a mixture of cyclic esters and chain esters, the cyclic ester is one or more of γ-butyrolactone, ethylene carbonate, propylene carbonate, and fluoroethylene carbonate; the chain ester is one or more of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, methylpropyl carbonate, methyl propionate, ethyl propionate, propyl propionate, methyl acetate, ethyl acetate, propyl acetate, methyl butyrate, ethyl butyrate, propyl butyrate, methyl fluoropropionate, ethyl fluoropropionate, and ethyl fluoroacetate.

9. The electrolyte according to claim 1, characterized in that: The lithium salt is lithium hexafluorophosphate; and / or the concentration of the lithium salt is 0.8 to 3 mol / L.

10. The electrolyte according to claim 1, characterized in that: The additives also include lithium salt additives, which are one or more of lithium tetrafluoroborate, lithium hexafluoroarsenate, lithium perchlorate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, lithium difluorophosphate, lithium trifluoromethylsulfonate, and lithium bis(fluorosulfonyl)imide; and / or, the lithium salt additives account for 0.1 to 5% of the total mass of the electrolyte.

11. A lithium battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The electrolyte is the electrolyte according to any one of claims 1 to 10.

12. The lithium battery according to claim 11, characterized in that: The active material of the positive electrode sheet is lithium cobalt oxide, and the charging cut-off voltage of the lithium battery can reach 4.5V or above.

Citation Information

Patent Citations

  • A device for distributing two fluids in a constant ratio and regulating the flow of the fluids

    EP0030049A1

  • Solenoid operated relief valve

    EP0030083A2

  • Catamenial pad

    EP0040085A2

  • Fuel injection pump for controlling the duration and timing of the injection

    EP0050053A2

  • Apparatus and method for treating work pieces

    EP0060055A1